Grassroot horizons : connecting participatory development initiatives, East and West - Morse, Richard, 1922-; Rahman, Anisur; Johnson, Kersten L. (Oxford & IBH Pub. Co., 1995)
Papers presented at various workshops by activists and researchers on a combined group action for overcoming poverty and oppression in developing and underdeveloped countries.